Viscosity Parameterization and the Gulf Stream Separation - Chassignet, Eric P.; Garraffo, Zulema D. (2001)
Recent advances in computer architecture allow for numerical integration of state-of-the-art ocean models at basin scale with a grid resolution of 1/10 degrees or higher. At that resolution, the Gulf Stream's separation at Cape Hatteras is well stimulated, but substantial differences from observations are still observed in its path, strength, and variability. Several high resolution (1/12 degrees) North Atlantic simulations performed with the Miami Isopycnic Coordinate Ocean Model (MICOM) are discussed and the results suggest that, even with such a fine grid spacing, the modeled large scale circulation is still quite sensitive to choices in forcing and viscosity parameterization. --Original contains color plates: All DTIC reproductions will be in black and white. Presented at the 'Aha Huliko'a Hawaiian Winter Workshop (12th) held in Honolulu, HI on 16-19 Jan 2001, p39-43. This article is from ADA412459 From Stirring to Mixing in a Stratified Ocean. Proceedings Hawaiian Winter Workshop (12th) Held in the University of Hawaii at Manoa on January 16-19, 2001